Study of genetic variation and its association with tensile strength among bamboo species through whole genome resequencing - Del Giudice, Lorenzo; Bazakos, Christos; Vassiliou, Michalis F. (Frontiers in Plant Science, 2022)
Moso bamboo (Phyllostachys edulis) is a versatile plant species that is widely used as a construction material by many low-income countries due to the lack of major construction materials such as steel and reinforced concrete. It is also widely used in China. Bamboo is an economically sustainable material that behaves exceptionally in natural disasters such as earthquakes and it can offer viable solutions for contemporary engineering challenges. Despite bamboo’s potential in the engineering sector, biological features such as its long generation time, its large genome size, and its polyploidy are constraining factors for genetic and genomic studies that potentially can assist the breeding efforts. This study re-sequenced 8 Phyllostachys species and 18 natural accessions of Ph. edulis, generating a large set of functionally annotated molecular markers (Single Nucleotide Polymorphisms (SNPs) and InDels) providing key genomic resource information. Moreover, all this genomic information was used to carry out a preliminary genome-wide association analysis and several candidate genes were identified to be correlated with a mechanical property that is of high interest to structural engineers: its tensile strength normal to its fibers (i.e., splitting).